High-strength and high-impact-toughness near-beta titanium alloy and preparation method and application thereof
By adjusting the content of elements in the titanium alloy and optimizing the heat treatment process, a near-β titanium alloy with heterogeneous sheet structure is formed, the problem of difficult balance of strength, plasticity and toughness in high temperature and high pressure and high corrosion environments is solved, and high strength and good toughness and plasticity are achieved.
Patent Information
- Application Number
- CN202510095838.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In the high temperature and high pressure and high corrosion environment, it is difficult to achieve a balance of strength, plasticity and toughness, which affects its further application in the petroleum industry.
By adjusting the content of elements such as Mo, Cr, Fe, Al, a high-strength, high-impact toughness near-beta titanium alloy is designed, and an optimized heat treatment process is used to form a heterogeneous sheet structure composed of a rough α sheet layer and a fine α sheet layer.
It significantly improves the tensile strength, yield strength, elongation of fracture and impact toughness of titanium alloy, and achieves excellent matching of strength, plasticity and toughness, and is suitable for the petroleum industry.
Smart Images

Figure CN119824275A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of titanium alloys, and in particular to a near-β titanium alloy with high strength and high impact toughness, and a preparation method and application thereof. Background Art
[0002] Titanium and titanium alloys are widely used in aerospace, chemical, medical and marine engineering fields due to their excellent performance. For example, titanium alloys have excellent corrosion resistance and can be used for a long time in extremely harsh environmental conditions, especially in corrosive environments such as seawater and acidic media. Its high specific strength, light weight and good high temperature performance make it a key material in high-tech fields such as engine turbine blades and aircraft structural parts.
[0003] In the field of petroleum industry, titanium alloy oil well pipe has excellent properties such as high specific strength, good corrosion resistance, low elastic modulus, easy cold forming, and seawater erosion resistance. Therefore, it is widely used in deep wells, ultra-deep wells, short radius horizontal wells and high acid oil and gas wells. At present, titanium alloy oil well pipe is mainly TC4.
[0004] However, with the continuous development of oil and gas exploration towards unconventional oil and gas resources such as deep water, high temperature and high pressure, and high corrosion, higher requirements are placed on the impact toughness and strength of oil well pipe materials. TC4, as an α+β type titanium alloy, can usually improve its strength through heat treatment, but the improvement of strength is often accompanied by a decrease in plasticity and impact toughness, and it is impossible to achieve a balance between strength, plasticity and toughness, which affects its further application in the field of oil industry. Summary of the invention
[0005] In view of this, the present invention provides a high-strength, high-impact toughness near-β titanium alloy and its preparation method and application. The near-β titanium alloy provided by the present invention has high strength, good plasticity and toughness, and has broad prospects in the field of petroleum industry.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A high-strength, high-impact toughness near-β titanium alloy, comprising the following chemical elements in percentage by mass: Mo: 3.2% to 4.5%, Cr: 2.5% to 4%, Fe: 0.5% to 1.8%, Al: 0.5% to 3%, and the balance being Ti and unavoidable impurities;
[0008] The molybdenum equivalent of the high-strength, high-impact toughness near-β titanium alloy is denoted as [Mo] eq , [Mo] eq The value is: 9<[Mo] eq <11;
[0009] Said[Mo] eq Obtained from formula I:
[0010] [Mo] eq =1[Mo]+1.6[Cr]+2.90[Fe]-1[Al];
[0011] Formula I;
[0012] In formula I, [Mo], [Cr], [Fe], and [Al] represent the mass percentage of each element in the high-strength, high-impact toughness near-β titanium alloy;
[0013] The metallographic structure of the high-strength, high-impact toughness near-β titanium alloy includes a coarse α lamella structure and a fine α lamella structure.
[0014] Preferably, the chemical elements include the following mass percentages: Mo: 3.58%, Cr: 2.97%, Fe: 1.06%, Al: 1.06%, and the balance is Ti and inevitable impurities.
[0015] Preferably, the chemical elements are included in the following mass percentages: Mo: 3.50%, Cr: 2.97%, Fe: 0.98%, Al: 2.01%, and the remainder is Ti and inevitable impurities.
[0016] Preferably, the high-strength, high-impact toughness near-β titanium alloy has a tensile strength greater than 1000 MPa, a yield strength greater than 900 MPa, a fracture elongation greater than 12%, and an impact toughness greater than 50 J / cm 2 .
[0017] The present invention also provides a method for preparing the high-strength, high-impact toughness near-β titanium alloy described in the above scheme, comprising the following steps:
[0018] According to the chemical element composition of the high-strength, high-impact toughness near-β titanium alloy described in the above scheme, the raw materials are melted to obtain a titanium alloy ingot;
[0019] The titanium alloy ingot is subjected to hot deformation processing to obtain a titanium alloy embryonic body;
[0020] The titanium alloy embryo is heat treated to obtain the high-strength, high-impact toughness near-β titanium alloy; the heat treatment includes sequentially performing a first heat preservation, a first cooling, a second heat preservation and a second cooling; the temperature of the first heat preservation is 800-900°C, and the heat preservation time is 1-4h; the first cooling is furnace cooling from the first heat preservation temperature to the second heat preservation temperature; the temperature of the second heat preservation is 500-600°C, and the heat preservation time is 4-8h; the second cooling is air cooling.
[0021] Preferably, the smelting is vacuum arc melting, the smelting temperature is 2000-2500° C., and the number of smelting times is 2-6 times.
[0022] Preferably, the thermal deformation process includes sequentially performing blank forging and hot rolling.
[0023] Preferably, the temperature of the blank forging is 1000-1200°C.
[0024] Preferably, the hot rolling temperature is 900-1000° C., the deformation per pass is 5%-10%, and the cumulative deformation is greater than 50%.
[0025] The present invention also provides the application of the high-strength, high-impact toughness near-β titanium alloy described in the above scheme or the high-strength, high-impact toughness near-β titanium alloy prepared by the preparation method described in the above scheme in the field of petroleum industry.
[0026] The present invention provides a high-strength, high-impact toughness near-β titanium alloy, comprising the following chemical elements in percentage by mass: Mo: 3.2% to 4.5%, Cr: 2.5% to 4%, Fe: 0.5% to 1.8%, Al: 0.5% to 3%, and the remainder being Ti and unavoidable impurities; the molybdenum equivalent of the high-strength, high-impact toughness near-β titanium alloy is denoted as [Mo] eq , [Mo] eq The value is: 9<[Mo] eq <11; The metallographic structure of the high-strength, high-impact toughness near-β titanium alloy includes coarse α lamellar structure and fine α lamellar structure. The currently used titanium alloys usually contain α phase and β phase, wherein the α phase is an HCP structure (hard) and the β phase is a BCC structure (soft). The hardness and modulus of the two are quite different, resulting in uncoordinated strain during deformation, and cracks are easily initiated at the β / α phase interface, thereby reducing the plasticity and toughness of the material. The present invention uses Mo, Cr, and Fe elements as β-stabilizing elements, which can not only stabilize the β phase, but also strengthen the β phase, effectively narrowing the gap in hardness and modulus between the β phase and the α phase, thereby alleviating the stress concentration at the interface between the β phase and the α phase, and improving the plasticity and toughness of the titanium alloy. Al, as the main α-stabilizing element, plays a role in strengthening the α phase and improving the strength of the material. At the same time, through a large number of studies, the present invention has found that when [Mo] eq When the temperature is between 9 and 11, the metastable β phase at high temperature can be retained to room temperature, and fine α phase can be precipitated after low-temperature aging, thereby significantly improving the strength of the alloy. Therefore, the present invention not only significantly improves the material strength through the design of the titanium alloy composition, but also effectively narrows the hardness and modulus gap between the two phases, alleviates the interface stress concentration phenomenon, and thus achieves a synergistic improvement in plasticity and toughness.
[0027] In addition, the titanium alloy provided by the present invention has a heterogeneous lamellar structure consisting of coarse α lamellae and fine α lamellae, wherein the coarse α lamellae are beneficial to improving plasticity and toughness, and the fine α lamellae can significantly improve the strength of the alloy. By regulating the structure of the titanium alloy, the plasticity and toughness of the titanium alloy are greatly improved while taking into account high strength.
[0028] The present invention also provides a method for preparing the high-strength, high-impact toughness near-β titanium alloy described in the above scheme. The present invention realizes the construction of a heterogeneous lamellar structure with coarse and fine α lamellae by optimizing the heat treatment process. The specific principle of heat treatment is as follows: first, heat treatment is performed in the β phase region to obtain a high-temperature β phase, and then during furnace cooling, due to the slow cooling rate, the α phase gradually grows to form a coarse α lamellae; finally, in the low-temperature aging stage (i.e., the second insulation), due to the low temperature, the growth rate of the α phase is limited, and fine α lamellae are precipitated. Through the above heat treatment method, a heterogeneous lamellar structure composed of coarse α lamellae and fine α lamellae is finally obtained, which greatly improves the plasticity and toughness of the titanium alloy while taking into account high strength.
[0029] In summary, the titanium alloy provided by the present invention has high strength as well as good plasticity and toughness, achieves an excellent match of strength, plasticity and impact toughness, and has broad application prospects in the field of petroleum industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM image of the high-strength, high-impact toughness near-β titanium alloy prepared in Example 1. DETAILED DESCRIPTION
[0031] The present invention provides a high-strength, high-impact toughness near-β titanium alloy, comprising the following chemical elements in percentage by mass: Mo: 3.2% to 4.5%, Cr: 2.5% to 4%, Fe: 0.5% to 1.8%, Al: 0.5% to 3%, and the balance being Ti and unavoidable impurities;
[0032] The molybdenum equivalent of the high-strength, high-impact toughness near-β titanium alloy is denoted as [Mo] eq , [Mo] eq The value is: 9<[Mo] eq <11;
[0033] Said[Mo] eq Obtained from formula I:
[0034] [Mo] eq =1[Mo]+1.60[Cr]+2.9[Fe]-1[Al];
[0035] Formula I;
[0036] In formula I, [Mo], [Cr], [Fe], and [Al] represent the mass percentage of each element in the high-strength, high-impact toughness near-β titanium alloy;
[0037] The metallographic structure of the high-strength, high-impact toughness near-β titanium alloy includes a coarse α lamella structure and a fine α lamella structure.
[0038] Unless otherwise specified, all raw materials / components used in the present invention are commercially available.
[0039] Calculated by mass percentage, the high-strength, high-impact toughness near-β titanium alloy provided by the present invention includes 3.2% to 4.5% Mo, preferably 3.5% to 4%, specifically 3.5% or 3.58%.
[0040] Calculated by mass percentage, the high-strength, high-impact toughness near-β titanium alloy provided by the present invention includes 2.5% to 4% Cr, preferably 2.8% to 3%, and specifically 2.97%.
[0041] Calculated by mass percentage, the high-strength, high-impact toughness near-β titanium alloy provided by the present invention includes Fe0.5% to 1.8%, preferably 0.8% to 1.2%, and specifically 0.98% or 1.06%.
[0042] In the present invention, the Mo, Cr, and Fe can stabilize and strengthen the β phase, effectively narrowing the gap in hardness and modulus between the β phase and the α phase, thereby alleviating stress concentration at the interface between the β phase and the α phase, and improving the plasticity and toughness of the titanium alloy.
[0043] The high-strength, high-impact toughness near-β titanium alloy provided by the present invention comprises 0.5% to 3% Al, preferably 1 to 2.1%, specifically 1.06% or 2.01%, in terms of mass percentage. In the present invention, the Al element can stabilize and strengthen the α phase and improve the strength of the titanium alloy.
[0044] Measured by mass percentage, the high-strength, high-impact toughness near-β titanium alloy provided by the present invention also includes a balance of Ti and unavoidable impurities.
[0045] In the present invention, the molybdenum equivalent of the high-strength, high-impact toughness near-β titanium alloy is denoted as [Mo] eq , [Mo] eq The value is: 9<[Mo] eq <11, specifically, the [Mo] eq The value of can be 9.084, 9.5, 9.6, 9.8, 10 or 10.346. In the present invention, [Mo] eq By controlling within the above range, the metastable β phase at high temperature can be retained to room temperature, and fine α phase can be precipitated after low-temperature aging, thereby significantly improving the strength of the titanium alloy.
[0046] In the present invention, the tensile strength of the high-strength, high-impact toughness near-β titanium alloy is greater than 1000MPa, preferably 1010-1064MPa, the yield strength is greater than 900MPa, preferably 905-957MPa, the elongation at break is greater than 12%, preferably 13%-15%, and the impact toughness is greater than 50J / cm 2 , preferably 51 to 56 J / cm 2 .
[0047] In the present invention, the metallographic structure of the high-strength, high-impact toughness near-β titanium alloy includes coarse α lamellae structure and fine α lamellae structure, the width of the coarse α lamellae structure is 0.6-1.9 μm, and the width of the fine α lamellae structure is 0.12-0.35 μm.
[0048] The present invention also provides a method for preparing the high-strength, high-impact toughness near-β titanium alloy described in the above scheme, comprising the following steps:
[0049] According to the chemical element composition of the high-strength, high-impact toughness near-β titanium alloy described in the above scheme, the raw materials are melted to obtain a titanium alloy ingot;
[0050] The titanium alloy ingot is subjected to hot deformation processing to obtain a titanium alloy embryonic body;
[0051] The titanium alloy embryo is heat treated to obtain the high-strength, high-impact toughness near-β titanium alloy.
[0052] The present invention melts the raw materials according to the chemical element composition of the high-strength, high-impact toughness near-β titanium alloy described in the above scheme to obtain a titanium alloy ingot. In the present invention, the raw materials are titanium particles, molybdenum particles, chromium particles, iron particles and aluminum particles; the purity of the raw materials is preferably ≥99.0%; the melting is preferably vacuum arc melting, the melting temperature is preferably 2000-2500°C, and the melting times are preferably 2-6 times, specifically 3 times.
[0053] After obtaining the titanium alloy ingot, the present invention performs hot deformation processing on the titanium alloy ingot to obtain a titanium alloy embryo. In the present invention, the hot deformation processing preferably includes performing open forging and hot rolling in sequence; the temperature of the open forging is preferably 1000-1200°C, specifically 1050°C, 1100°C or 1150°C. The present invention preferably first keeps the titanium alloy ingot at the temperature of the open forging for 1 hour, and then performs open forging; in a specific embodiment of the present invention, a rod-shaped sample with a length of 300 mm, a width of 60 mm, and a thickness of 40 mm is obtained by open forging.
[0054] In the present invention, the hot rolling temperature is preferably 900-1000°C, specifically 900°C, 950°C or 1000°C, the hot rolling deformation is preferably 5%-10%, and the cumulative deformation is preferably greater than 50%, specifically 60%.
[0055] After obtaining the titanium alloy embryo, the present invention heat treats the titanium alloy embryo to obtain the high-strength, high-impact toughness near-β titanium alloy. In the present invention, the heat treatment includes sequentially performing the first heat preservation, the first cooling, the second heat preservation and the second cooling; the temperature of the first heat preservation is 800-900°C, specifically 850°C, and the heat preservation time is 1-4h, specifically 1h, 2h, 3h or 4h; the first cooling is furnace cooling from the temperature of the first heat preservation to the temperature of the second heat preservation; the temperature of the second heat preservation is 500-600°C, specifically 550°C, and the heat preservation time is 4-8h, specifically 4h, 5h, 6h, 7h or 8h; the second cooling is air cooling. The present invention can obtain a heterogeneous lamellar structure composed of coarse α lamellae and fine α lamellae through the above-mentioned heat treatment method, which greatly improves the plasticity and toughness of the titanium alloy while taking into account high strength.
[0056] The present invention also provides the application of the high-strength, high-impact toughness near-β titanium alloy described in the above scheme or the high-strength, high-impact toughness near-β titanium alloy prepared by the preparation method described in the above scheme in the field of petroleum industry. The titanium alloy provided by the present invention has high strength, good plasticity and impact toughness, and has broad application prospects in the field of petroleum industry.
[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] Example 1
[0059] This embodiment provides a high-strength, high-impact toughness near-β titanium alloy. The chemical element composition of the titanium alloy, measured in percentage by mass, is: Mo: 3.58%, Cr: 2.97%, Fe: 1.06%, Al: 1.06%, and the remainder is Ti and unavoidable impurities.
[0060] The preparation method of the titanium alloy is as follows: high-purity titanium, molybdenum, chromium, iron, and aluminum particles are used to prepare raw materials according to the composition ratio, and vacuum arc melting is used to repeatedly melt 3 times to obtain a titanium alloy ingot; the titanium alloy ingot is kept at 1050°C for 1 hour, and then the blank is forged to obtain a rod sample with a length of 300 mm, a width of 60 mm, and a thickness of 40 mm; then hot rolling is carried out at 900°C, with a deformation of 10% per pass and a total deformation of 60%; the hot-rolled sample is placed in a vacuum tube furnace at 850°C for heat treatment for 1 hour, and then the furnace is cooled to 550°C, and then kept at 550°C for 6 hours, and air-cooled to obtain a high-strength, high-impact toughness near-β titanium alloy.
[0061] Mechanical properties test samples were cut from the prepared high-strength, high-impact toughness near-β titanium alloy sample, where the tensile test sample was a plate-shaped sample with a gauge length of 25 mm, a width of 5, and a thickness of 2 mm; the impact test sample was a 55 mm × 10 mm × 10 mm V-notch sample. The mechanical properties test results show that the tensile strength of the high-strength, high-impact toughness near-β titanium alloy prepared in this embodiment is 1010 MPa, the yield strength is 905 MPa, the elongation at break is 15%, and the impact toughness is 56 J / cm 2 .
[0062] Figure 1 is a SEM image of the high-strength, high-impact toughness near-β titanium alloy prepared in this embodiment. Figure 1 It can be seen that the structure of the titanium alloy prepared in this embodiment is a heterogeneous lamellar structure, which contains two forms of α phase: fine α lamellae and coarse α lamellae. The fine α lamellae can improve the strength of the alloy, while the coarse α lamellae can effectively hinder the expansion of cracks and improve the impact toughness and plasticity of the alloy.
[0063] Example 2
[0064] This embodiment provides a high-strength, high-impact toughness near-β titanium alloy. The chemical element composition of the titanium alloy is, by mass percentage, Mo: 3.50%, Cr: 2.97%, Fe: 0.98%, Al: 2.01%, and the remainder is Ti and unavoidable impurities.
[0065] The preparation method of the titanium alloy is as follows: high-purity titanium, molybdenum, chromium, iron, and aluminum particles are used to prepare raw materials according to the composition ratio, and vacuum arc melting is used to repeatedly melt 3 times to obtain a titanium alloy ingot; the titanium alloy ingot is kept at 1050°C for 1 hour, and then the blank is forged to obtain a rod sample with a length of 300 mm, a width of 60 mm, and a thickness of 40 mm; then hot rolling is carried out at 900°C, with a deformation of 10% per pass and a total deformation of 60%; the hot-rolled sample is placed in a vacuum tube furnace at 850°C for heat treatment for 1 hour, then furnace cooled to 550°C, and then kept at 550°C for 6 hours, and air cooled to obtain a high-strength, high-impact toughness near-β titanium alloy.
[0066] Mechanical properties test samples were cut from the prepared high-strength, high-impact toughness near-β titanium alloy sample, where the tensile test sample was a plate-shaped sample with a gauge length of 25 mm, a width of 5, and a thickness of 2 mm; the impact test sample was a 55 mm × 10 mm × 10 mm V-notch sample. The mechanical properties test results show that the tensile strength of the high-strength, high-impact toughness near-β titanium alloy prepared in this embodiment is 1064 MPa, the yield strength is 957 MPa, the elongation at break is 13%, and the impact toughness is 51 J / cm 2 .
[0067] Comparative Example 1
[0068] This comparative example provides an α+β type titanium alloy. The chemical element composition of the titanium alloy is as follows, in terms of mass percentage: Al: 5.84%, V: 4.05%, and the remainder is Ti and unavoidable impurities.
[0069] The preparation method of α+β titanium alloy is as follows: high-purity titanium, vanadium and aluminum particles are used to prepare raw materials according to the composition ratio, and vacuum arc melting is used to repeatedly melt for 3 times to obtain an ingot; the smelted ingot is kept at 1050°C for 1 hour, and then the blank is forged to obtain a rod sample with a length of 300 mm, a width of 60 mm and a thickness of 40 mm; then hot rolling is carried out at 900°C, with a deformation of 10% per pass and a total deformation of 60%; the hot-rolled sample is placed in a vacuum tube furnace at 850°C for heat treatment for 1 hour, then furnace cooled to 550°C, and then kept at 550°C for 6 hours, and air cooled to obtain an α+β titanium alloy.
[0070] The mechanical properties test samples of the prepared α+β titanium alloy were cut, of which the tensile test samples were plate-shaped samples with a gauge length of 25mm, a width of 5, and a thickness of 2mm; the impact test samples were 55mm×10mm×10mm V-notch samples. The mechanical properties test results show that the tensile strength of the α+β titanium alloy is 975MPa, the yield strength is 868MPa, the elongation at break is 12%, and the impact toughness is 47J / cm 2 .
[0071] The mechanical property test results of the titanium alloys prepared in Examples 1 to 2 and Comparative Example 1 are summarized in Table 1.
[0072] Table 1 Summary of mechanical properties test results
[0073]
[0074] It can be seen from the results in Table 1 that the titanium alloy prepared in the present invention has higher tensile strength, yield strength, elongation and impact toughness than that of Comparative Example 1.
[0075] In summary, the present invention effectively reduces the hardness and modulus gap between the β phase and the α phase by controlling the content of Mo, Cr, Fe, and Al strengthening elements, thereby improving strength and toughness. At the same time, by optimizing the heat treatment process, a heterogeneous lamellar structure with coarse and fine α layers is prepared, which greatly improves the plasticity and toughness of the titanium alloy while taking into account high strength, achieving excellent matching of strength, plasticity, and impact toughness, and has broad prospects in the field of petroleum industry.
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength, high-impact toughness near-β titanium alloy, characterized in that: The chemical elements include the following mass percentages: Mo: 3.2% to 4.5%, Cr: 2.5% to 4%, Fe: 0.5% to 1.8%, Al: 0.5% to 3%, and the balance is Ti and unavoidable impurities; The molybdenum equivalent of the high-strength, high-impact toughness near-β titanium alloy is denoted as [Mo] eq , [Mo] eq The value is: 9<[Mo] eq <11; Said[Mo] eq Obtained from formula I: [Mo] eq =1[Mo]+1.6[Cr]+2.90[Fe]-1[Al]; Formula I; In formula I, [Mo], [Cr], [Fe], and [Al] represent the mass percentage of each element in the high-strength, high-impact toughness near-β titanium alloy; The metallographic structure of the high-strength, high-impact toughness near-β titanium alloy includes a coarse α lamella structure and a fine α lamella structure.
2. The high-strength, high-impact toughness near-β titanium alloy according to claim 1, characterized in that: The chemical elements include the following mass percentages: Mo: 3.58%, Cr: 2.97%, Fe: 1.06%, Al: 1.06%, and the balance is Ti and inevitable impurities.
3. The high-strength, high-impact toughness near-β titanium alloy according to claim 1, characterized in that: The chemical elements include the following mass percentages: Mo: 3.50%, Cr: 2.97%, Fe: 0.98%, Al: 2.01%, and the balance is Ti and inevitable impurities.
4. The high-strength, high-impact toughness near-β titanium alloy according to claim 1, characterized in that: The high-strength, high-impact toughness near-β titanium alloy has a tensile strength greater than 1000 MPa, a yield strength greater than 900 MPa, a fracture elongation greater than 12%, and an impact toughness greater than 50 J / cm 2 .
5. The method for preparing the high-strength, high-impact toughness near-β titanium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: According to the chemical element composition of the high-strength, high-impact toughness near-β titanium alloy as claimed in any one of claims 1 to 4, the raw materials are melted to obtain a titanium alloy ingot; The titanium alloy ingot is subjected to hot deformation processing to obtain a titanium alloy embryonic body; The titanium alloy embryo is heat treated to obtain the high-strength, high-impact toughness near-β titanium alloy; the heat treatment includes sequentially performing a first heat preservation, a first cooling, a second heat preservation and a second cooling; the temperature of the first heat preservation is 800-900°C, and the heat preservation time is 1-4h; the first cooling is furnace cooling from the first heat preservation temperature to the second heat preservation temperature; the temperature of the second heat preservation is 500-600°C, and the heat preservation time is 4-8h; the second cooling is air cooling.
6. The preparation method according to claim 5, characterized in that: The smelting is vacuum arc smelting, the smelting temperature is 2000-2500° C., and the smelting times are 2-6 times.
7. The preparation method according to claim 5, characterized in that: The thermal deformation process includes sequentially performing blank forging and hot rolling.
8. The preparation method according to claim 7, characterized in that: The temperature of the blank forging is 1000-1200°C.
9. The preparation method according to claim 7, characterized in that: The hot rolling temperature is 900-1000° C., the deformation amount per pass is 5%-10%, and the cumulative deformation amount is greater than 50%.
10. Application of the high-strength, high-impact-toughness near-β titanium alloy according to any one of claims 1 to 4 or the high-strength, high-impact-toughness near-β titanium alloy prepared by the preparation method according to any one of claims 5 to 9 in the field of petroleum industry.
Citation Information
Patent Citations
A near-β-type titanium alloy with high strength and high impact toughness and its preparation method
CN106507833B
Heat-resistant titanium alloy, and engine valve formed using it
JP2006283062A
Alpha + beta type titanium alloy, process for producing titanium alloy, process for coil rolling, and process for producing cold-rolled coil of titanium alloy
US20010041148A1
Heat-Treatment of an Alloy for a Bearing Component
US20140116581A1